2022
DOI: 10.3390/life12121960
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Derivatives in Combating Spinal Cord Injury: A Mechanistic and Systematic Review

Abstract: Spinal cord injury (SCI) possesses a complicated etiology. There is no FDA-approved treatment for SCI, and the majority of current interventions focus on reducing symptoms. During SCI, inflammation, oxidative stress, apoptosis, and autophagy are behind the secondary phase of SCI and cause serious consequences. It urges the need for providing multi-targeting agents, that possess lower side effects and higher efficacy. The plant secondary metabolites are multi-targeting agents and seem to provide new roads in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…Quercetin can exert neuroprotective effects by preventing oxidative stress-induced neural toxicity (Fakhri et al, 2022), and it was experimentally indicated to be beneficial for managing long COVID. However, no human studies have provided definitive evidence to support F I G U R E 3 Risk of bias for two clinical studies of quercetin.…”
Section: Experimental Results Regarding Quercetin Against Long Covid ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin can exert neuroprotective effects by preventing oxidative stress-induced neural toxicity (Fakhri et al, 2022), and it was experimentally indicated to be beneficial for managing long COVID. However, no human studies have provided definitive evidence to support F I G U R E 3 Risk of bias for two clinical studies of quercetin.…”
Section: Experimental Results Regarding Quercetin Against Long Covid ...mentioning
confidence: 99%
“…SARS‐CoV‐2 infection can induce oxidative stress (Alam & Czajkowsky, 2022) which is related to the inflammatory response and to long COVID syndrome. The antioxidant capacity of quercetin has been extensively studied (Bentz, 2017; Fakhri et al, 2022; Pourteymour Fard Tabrizi et al, 2020). Quercetin can increase the levels of antioxidant enzymes such as SOD, CAT, POD, GR, GSHPX, and NADPH oxidase, offering protection against oxidative stress (Pourteymour Fard Tabrizi et al, 2020).…”
Section: Brief Review Of Quercetinmentioning
confidence: 99%
“…Also, in this study, quercetin supplementation concentration-dependently increased horizontal locomotion, self grooming and radial arm maze spatial working memory, while at both concentrations of quercetin, an anxiolytic effect and increase in Y maze spatial working memory was observed. Quercetin's ability to reverse brain injury has been reported severally (85)(86)(87)(88)(89)(90).…”
Section: Discussionmentioning
confidence: 99%
“…Although some reports showed that quercetin is effective in the treatment of spinal cord injury [ 18 ], the key pathways and genes involved in the repair of spinal cord injury are still unclear. Based on the complex interactions and influences between drug molecules and different intracellular pathways in SCI, network pharmacology analysis was used to explore the targets and potential mechanisms of quercetin in SCI repair.…”
Section: Introductionmentioning
confidence: 99%